Using Watershed Boundaries to Map Adverse Health Outcomes: Examples From Nebraska, USA. (23rd January 2018) - Corley, Brittany; Bartelt-Hunt, Shannon; Rogan, Eleanor; Coulter, Donald; Sparks, John; Baccaglini, Lorena; Howell, Madeline; Liaquat, Sidra; Commack, Rex; Kolok, Alan S
In 2009, a paper was published suggesting that watersheds provide a geospatial platform for establishing linkages between aquatic contaminants, the health of the environment, and human health. This article is a follow-up to that original article. From an environmental perspective, watersheds segregate landscapes into geospatial units that may be relevant to human health outcomes. From an epidemiologic perspective, the watershed concept places anthropogenic health data into a geospatial framework that has environmental relevance. Research discussed in this article includes information gathered from the literature, as well as recent data collected and analyzed by this research group. It is our contention that the use of watersheds to stratify geospatial information may be both environmentally and epidemiologically valuable.